The The Effect of Using Led Lights (Light Emitting Diode) in the Operation of Bottom Gillnets on Catches In Pangandaran Waters, West Java - Ginanjar, Martin Anjar; Suyasa, I Nyoman; Dewi, Ita Junita Puspa (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The objectives of the study were to analyse the response of dominant fish to different light colours that reflect the wavelength of light and to analyse the species composition of the gillnet catch to determine the fish that are positively phototaxis to LED light. Data collection was conducted using the experimental method. The experimental design used 1 unit of bottom gillnet gear with a mesh size of 4 inches, and used LED (Light Emitting Diode) lights. Trials using green LED lights and white LED lights were operated simultaneously between the control gillnet (without LED lights) and the experimental gillnet (with LED lights). The results of statistical analysis of gillnet catches with green LED light aids with white LED light aids and control nets have a significant effect on the number of gillnet catches. The results were: (1) The number of fish caught at a distance of < 1 m and at a distance of 1-2 m, this proves that many fish are attracted to light (positive phototaxis); (2) Proven by gill net fishing gear using green LED light aids obtained fish weighing up to 77.7 kg. (3) It is proven that the distance of the lamp with the position of the fish caught on the net sheet can produce the highest weight of fish caught, on green LED lights at a distance of <1 m the weight of the fish reached 30.89 kg.